Auto-biographic method – “Case Study” – Australian Slovenes - Čebulj Sajko, Breda (Two Homelands, 2001)
The author explains on the case of researching the life of Australian Slovenes some, mainly foreign, ethnological and anthropological definitions of autobiography. Čebulj Sajko Breda presents the stand-point of Slovene researchers towards this type of sources in the second part of her contribution. Despite an increased interest for a thorough theoretical knowledge about life stories we yet do not have an answer to the question what autobiography is.